2005
DOI: 10.1513/pats.200504-028sr
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Airway Smooth Muscle in the Pathogenesis of Airway Wall Remodeling in Chronic Obstructive Pulmonary Disease

Abstract: Airway wall remodeling processes are present in the small airways of patients with chronic obstructive pulmonary disease, consisting of tissue repair and epithelial metaplasia that contribute to airway wall thickening and airflow obstruction. With increasing disease severity, there is also increased mucous metaplasia and submucosal gland hypertrophy, peribronchial fibrosis, and an increase in airway smooth muscle mass. Apart from its contractile properties, airway smooth muscle produces inflammatory cytokines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 107 publications
3
92
0
10
Order By: Relevance
“…Airway smooth muscle cells not only have contractile properties but also are capable of expressing and releasing cytokines, chemokines, growth factors and proteases [135,136], and can participate in the inflammatory and remodelling process [137]. Airway smooth muscle cells also produce matrix proteins, and their behaviour may depend upon interactions with their own matrix [138].…”
Section: Airway Smooth Musclementioning
confidence: 99%
“…Airway smooth muscle cells not only have contractile properties but also are capable of expressing and releasing cytokines, chemokines, growth factors and proteases [135,136], and can participate in the inflammatory and remodelling process [137]. Airway smooth muscle cells also produce matrix proteins, and their behaviour may depend upon interactions with their own matrix [138].…”
Section: Airway Smooth Musclementioning
confidence: 99%
“…In addition, cigarette smoke directly stimulates various types of cells, in particular macrophages [40,41] and epithelial cells of the airways [42], thus contributing to increased production of mediators and cytokines that participate in maintaining the inflammatory reaction. Through their interactions with the epithelium and extracellular matrix, the bronchial smooth muscle cells would also appear to play an important role in the remodelling of the airways observed in COPD [43].…”
Section: Active and Passive Smokingmentioning
confidence: 99%
“…The airway smooth muscle cell is increasingly recognised as an important cellular source of pro-inflammatory cytokines and growth factors, including interleukins (IL)-6 and -8, monocyte chemoattractant protein (MCP)-1, vascular endothelial growth factor (VEGF) and others (see [15][16][17] for review) and it appears to play an important immunomodulatory role in airways diseases such as asthma and COPD. The immunomodulatory function of airway smooth muscle has mostly been studied in cell culture; these studies have revealed that Gprotein-coupled receptor agonists, growth factors, cytokines and extracellular matrix proteins can induce the release of significant amounts of pro-inflammatory cytokines [15][16][17].…”
mentioning
confidence: 99%
“…The immunomodulatory function of airway smooth muscle has mostly been studied in cell culture; these studies have revealed that Gprotein-coupled receptor agonists, growth factors, cytokines and extracellular matrix proteins can induce the release of significant amounts of pro-inflammatory cytokines [15][16][17]. In addition, airway smooth muscle cells exhibit IL-8 release in response to cigarette smoke extract, which is strongly augmented by cytokines such as tumour necrosis factor (TNF)-a [18].…”
mentioning
confidence: 99%